Factors influencing gender equity in ecosystem restoration: A three-country analysis - Chhem, Remy; Elias, Marlene; Thomas, Evert; Ekue, Marius; Gata, Larissa; Cerron, Jessica; Manga Essouma, Francois; Lora, Ikeda (Commonwealth Forestry Association, 2025)
Ecosystem restoration is a promising antidote to land and forest degradation and deforestation. Yet, achieving the ecological, social and economic promise of restoration in an equitable way hinges upon socio-institutional factors that remain poorly addressed in restoration theory and practice. This study examines the factors shaping gender equity across 17 restoration projects in Cameroon, Peru and the Philippines. Qualitative data collected through key informant interviews and focus group discussions are interpreted using a framework that highlights the recognition, procedural and distributional dimensions of gender equity. Findings show that intersecting factors related to gender, land ownership, and membership in associations drive exclusion from, and inequity in, restoration initiatives. The cases reveal the promise of local associations, and the need to promote clear and secure land tenure, the active engagement of local women and men, and transparency in the distribution of benefits to pave the way for equitable restoration initiatives.